2022
DOI: 10.1017/s0950268821002788
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of transmission routes of COVID-19 cluster infections in Gangwon Province, Korea

Abstract: This study investigated the characteristics of transmission routes of COVID-19 cluster infections (⩾10 linked cases within a short period) in Gangwon Province between 22 February 2020 and 31 May 2021. Transmission routes were divided into five major categories and 35 sub-categories according to the relationship between the infector and the infectee and the location of transmission. A total of 61 clusters occurred during the study period, including 1741 confirmed cases (55.7% of all confirmed cases (n = 3125)).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Other studies showed that housing conditions, such as overcrowded housing, are an important risk factor for SARS-CoV-2 infection [ 1 , 26 ]. Household exposure can be a relevant risk factor for SARS-CoV-2 infection in patients who rarely leave their home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that housing conditions, such as overcrowded housing, are an important risk factor for SARS-CoV-2 infection [ 1 , 26 ]. Household exposure can be a relevant risk factor for SARS-CoV-2 infection in patients who rarely leave their home.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no other study demonstrated that specifically the number of cohabitants also increases the risk in PwMS. This result is particularly challenging if we consider that reduced human interaction related to COVID-19 has a profound impact on organic and mental health [ 1 , 26 , 27 ]. Although it is associated with an increased risk of COVID-19 infection, we still encourage social interactions between PwMS and their relatives, but we recommend strict adherence to COVID-19 preventive measures, such as FFP2 mask wearing and frequent hand sanitizing.…”
Section: Discussionmentioning
confidence: 99%
“… Lim et al (2022) showed that 55.7% of confirmed cases were caused by mass infection, which occurred in various facilities such as restaurants, sports facilities, and entertainment businesses. To prevent mass infection, the Korean government has prohibited private gatherings of more than five people in most places, including restaurants and party rooms, on December 23, 2020.…”
Section: Datamentioning
confidence: 99%
“…Alongside timely diagnosis, the WHO and European Centre for Disease Prevention and Control (ECDC) advised to detect variant circulation using SARS-CoV-2 whole-genome or spike (S), partial or complete, gene sequencing [ 8 ]. Phylogenetic analysis of newly generated sequences combined with epidemiological and clinical data was a key tool to understand the transmissibility pathway of this pandemic virus and to manage public health measures against COVID-19 disease [ 9 , 10 ]. In March 2020, the Global Initiative on Sharing All Influenza Data (GISAID) database started to share SARS-CoV-2 genomes from Turkey, contributing to the performance of molecular characterization and to evaluate the prevalence and diffusion of variants in this specific geographic area [ 4 ].…”
Section: Introductionmentioning
confidence: 99%